The Preventing Bronchial Asthma Relapses Through Alternate Nostril Breathing at the Aek Raso Community Health Center: Alternate Nostril Breathing - Lubis, Zulfahri; Sukma, Sukma Yunita; Masdalifa, Masdalifa Pasaribu (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
The main complaint that often occurs in asthma sufferers is shortness of breath, shortness of breath occurs due to narrowing of the airways due to hyperreactivity of the airways which can cause bronchospasm, persistent inflammatory cell infiltration, mucosal edema and thick mucus hypersecretion. This community service was carried out by providing counseling to 20 asthma patients for one day with a duration of 30 minutes. After the administration of alternate nostril breathing, there was a decrease in the degree of shortness of breath in all participants. This alternate nostril breathing intervention is effective in preventing bronchial asthma recurrence and is recommended as an adjunct to pharmacological intervention.